Sistema corporativo de produção: um estudo de caso do sistema produtivo da General Motors, utilizando as dimensões competitivas - Luz, Daniel Fonseca da (Universidade do Vale do Rio dos Sinos, 2011)
This work focused on the automotive industry and underpinned in academic literature, proposes to revisit concepts and models of production systems from the point of view of corporate production systems. In this work, the corporate production system of General Motors, the GMS - Global Manufacturing System, was analyzed using the methodology of case study, which studied aspects of its construction and implementation. Dimensions such: cost, quality, flexibility, speed and reliability of delivery, customer service, innovativeness and security operations were evaluated by the managers of General Motors Brazil, plant Gravataí-RS. Among the dimensions mentioned above respondents were encouraged to choose five of the most contributory to the GMS and those who somehow be represented winning or qualifying order. From the choice of the most relevant dimensions, assessed how the 33 elements that constitute the GMS contribute to the production of the company competitive in every dimension and if they somehow represent trade-offs for the system. These elements were scattered in their use, and implementation inconsistencies in manufacturing environment assessed. It is considered that the presented study approximates the operational approaches to the academic designs, avoiding the implementation of initiatives ineffective and inconsistent with the macro objectives of corporate production systems.
Keywords: Indústria automotiva; Alinhamento de estratégia; Sistemas corporativos de produção; Dimensões competitivas; Automotive industry; Alignment of strategy; Corporation production system; Competitive dimensions; ACCNPQ::Engenharias::Engenharia de Produção